2019
DOI: 10.1093/eurpub/ckz041
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvanted influenza vaccine for the Italian elderly in the 2018/19 season: an updated health technology assessment

Abstract: Background The elderly, defined here as subjects aged ≥ 65 years, are among at-risk subjects for whom annual influenza vaccination is recommended. For the 2018/19 season, three vaccine types are available for the elderly in Italy: trivalent inactivated vaccine (TIV), adjuvanted TIV (aTIV) and quadrivalent inactivated vaccines (QIV). No health technology assessment (HTA) of seasonal influenza vaccination in the elderly has previously been conducted in Italy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…On the other hand, evidence has been presented that the use of QIV in the >64-year age group would result in higher costs and lower health benefits than the use of aTIV [28]. An Italian Health Technology Assessment has also indicated that the use of aTIV in the elderly seems to be the best choice [29]. QIV may not result in a significant advantage in the elderly because aTIV can produce substantial cross-protection between the two linages of IBV, independent of the match between the circulating strain and the vaccine strain [3034].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, evidence has been presented that the use of QIV in the >64-year age group would result in higher costs and lower health benefits than the use of aTIV [28]. An Italian Health Technology Assessment has also indicated that the use of aTIV in the elderly seems to be the best choice [29]. QIV may not result in a significant advantage in the elderly because aTIV can produce substantial cross-protection between the two linages of IBV, independent of the match between the circulating strain and the vaccine strain [3034].…”
Section: Discussionmentioning
confidence: 99%
“…For the 2019 to 2020 influenza season, a quadrivalent cell-based influenza vaccine (QIV) was available for the first time in Italy and the rest of Europe, in addition to the trivalent inactivated vaccine (TIV) and the adjuvanted TIV. 2,3 The QIV vaccine uses the Madin-Darby Canine Kidney (MDCK) cell line, instead of fertilized chicken eggs, for growing the influenza virus. 4 The MDCK cell line is made available to vaccine manufacturers from cell banks that have produced the cell line in accordance with good manufacturing practice guidelines, and has been tested for purity, identity, and for the absence of contaminating viruses as required by Food and Drug Administration, EMMA, and World Health Organization guidelines.…”
Section: Epidemiological Evidence For Association Between Higher Inflmentioning
confidence: 99%
“…Over several decades, the paradigm was and still is that aging is related to the shrinkage of naïve T cells, which explains why certain diseases are increasing such as infection, cancer are increasing and why older subjects are not able to respond to the vaccination as efficiently as young subjects [ 49 , 50 ]. This is most notably the case for the influenza vaccine [ 51 54 ], though recently this idea has been seriously challenged by the introduction of various adjuvanted new vaccines with greater efficacy in the elderly [ 55 , 56 ]. The decrease in naive T cells, which never encountered their cognate antigens, results in a decrease of T cell repertoire (oligoclonality of the TCR) which are unable to recognize a fully new antigen such as those arising from cancer (neoantigens) [ 57 ].…”
Section: Immune Changes With Agingmentioning
confidence: 99%